Abundance and distribution of cigarette butts on the sand of five touristic beaches in Latin America during the COVID-19 pandemic (2023)
Cigarette butts (CB) and cigarette butt fibers (CBF) are highly abundant and frequent residues on beach sand. Also, they are hazardous waste due to their significant toxicity and potential risk to the ecosystems’ biota and the health of beach tourists. This study aimed to determine the abundance and density of CB and CBF found on the active, rest, and service zones of five pilot beaches in Argentina, Colombia, Brazil, Ecuador, and Mexico. The methodology involved collecting CB and CBF in 500 m2 transects of urban tourist beaches using a citizen scienceadapted methodology between June 2021 and May 2022, during the COVID-19 pandemic. The abundance and density of CB and CBF, and the Cigarette Butt Pollution Index (CBPI) were calculated. The highest proportion of CB was found in service and rest areas. Bocagrande (CO) reported the highest generation of CB and CBF and a severe CBPI.